CBM20CP, a novel functional protein of starch metabolism in green algae - Velázquez, María Belén (2021)
Ostreococcus tauri is a marine picoalga, the smallest free-living eukaryotic and the simplest photosynthetic organism described to date, which has a single chloroplast and mitochondrion. The O. tauri genome codes for less than 8000 genes with low genetic redundancy, however, the pathway of starch metabolism would be conserved. This alga has all the enzymes that participate in the synthesis of starch in higher plants encoded in its genome, at least one ADPGlucose pyrophosphorylase (ADPGlc PPase), one GBSS, SSs I-III (SSI, II, and III), SBEI-II and ISA1- found. It is well known that SSIV regulates the number of starch granules in Arabidopsis and would also participate in the initiation of starch synthesis. The fact that O. tauri contains a single starch granule could be related to the lack of this enzyme. Moreover, we previously described the presence of three different isoforms of SSIII with a variable number of Starch binding domains (SBDs), suggesting that the synthesis and regulation of starch metabolism in this organism is highly complex. SBDsare a special subfamily of CBMs that bind to starch and have acquired the evolutionary advantage of being able to disrupt the surface of their substrate due to the presence of two binding sites. These domains have been classified into thirteen families, in special SBDs included in CBM20 family were first found in starch hydrolases, however, they are present in several amylolytic and non-amylolytic enzymes from plants, mammals, archaea, bacteria, and fungi. In general, CBM20 are attached also to a CD and many of them have regulatory functions and a moderate affinity to starch. Only few proteins from algae containing a CBM20 have been characterized, such a laforin homolog from the red algae Chondrus crispus and a the SAGA1 protein from C. reinhardtii, which is involved in shaping starch plates. Although the O.tauri genome is fully sequenced, there are still many genes and proteins to which no function was assigned. Here, we identify the OT_ostta06g01880 gene that encodes CBM20CP, a plastid protein which contains a central carbohydrate binding domain of the CBM20 family, a coiled coil domain at the C-terminus and lacks catalytic activity. We demonstrate that CBM20CP has the ability to bind starch, amylose and amylopectin with different affinities. Furthermore, this protein interacts with OsttaSSIII-B, increasing its binding to starch granules, its catalytic efficiency and promoting granule growth. The results allow us to postulate a regulatory role for CBM20CP in starch metabolism in green algae.